The Revealing Accounting For Waste Entrepreneurs Seen From Sharia Perspective - Dyatri Utami Arina Absari (CV. AFDIFAL MAJU BERKAH, 2024)
Garbage is a problem that must be faced by the public due to discharges of waste is generated from human activities unused (Yansen & Arnatha, 2012). Waste problem is to encourage the growth Of public awareness to participate take part in waste management (Utami & Indrasti, 2008). According to (Adnan, 1995: 47) side of science, accounting is actually a domain